(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the formation of France as a secular state and the constitutional – legal experience. Analyzes the legal concept of «laicism» «Secularism», «secular state». We consider the formation of France as a secular state. The article has an interdisciplinary nature. The author examines the theoretical and practical problems of becoming France as a secular state. And also it gives a description of the current state of relations between the state and religion in France. The significance of the constitutional-legal regulation. Analyze the features of influence of the French model of laicism in the formation of Kazakhstan as a secular state. Key words: France, France as a secular state, Constitution of France, secularism, secular state, the relationship between state and religion, separation of state and religion.